Vuelta y Vuelta - Memorias del Exilio Chileno - Bichl, Daniela; Toth, Markus (Austria, 2013)
During the 17 years of dictatorship in Chile, hundreds of thousands of Chileans were forced to leave their country. Three collective theatre workshops in Sweden, Austria and Chile were the starting point to work on topics like exile and its further consequences with some of the Chileans.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films